PERAN MEDIASI KEPUASAN KONSUMEN PADA PENGARUH KUALITAS PRODUK TERHADAP NIAT BELI ULANG - Dewi, Komang Ayu Trishantika; Piartrini, Putu Saroyini (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The presence of the Covid-19 pandemic has made changes to people's lifestyles, one of which is a healthy lifestyle. Health is one of the priority needs for the whole community. A healthy lifestyle is a form of a person's behavior associated with health that can be measured by eating organic food, health care and life balance. This study aims to determine the mediating role of consumer satisfaction on the effect of product quality on the repurchase intention of Herbalife Nutritional Shake Mix products in Denpasar City by using the Disconfirmation Expectation Theory approach. The sampling technique used in this research is non-probability sampling. Based on survey data from 224 Herbalife Nutritional Shake Mix consumers in Denpasar City, the results of Baron and Kenny Steps regression analysis reveal that product quality has a positive and significant effect on consumer satisfaction. Consumer satisfaction has a positive and significant effect on repurchase intentions. Product quality has a positive and significant effect on repurchase intention. Consumer satisfaction partially mediates the effect of product quality on repurchase intentions. The implications of this finding can be a reference for Herbalife companies to achieve profits and increase sales by paying attention to product quality and consumer satisfaction so that consumers will continue to repurchase Herbalife Nutritional Shake Mix products